2016
DOI: 10.1111/tpj.13201
|View full text |Cite
|
Sign up to set email alerts
|

System level analysis of cacao seed ripening reveals a sequential interplay of primary and secondary metabolism leading to polyphenol accumulation and preparation of stress resistance

Abstract: SUMMARYTheobroma cacao and its popular product, chocolate, are attracting attention due to potential health benefits including antioxidative effects by polyphenols, anti-depressant effects by high serotonin levels, inhibition of platelet aggregation and prevention of obesity-dependent insulin resistance. The development of cacao seeds during fruit ripening is the most crucial process for the accumulation of these compounds. In this study, we analyzed the primary and the secondary metabolome as well as the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 79 publications
0
36
0
3
Order By: Relevance
“…Variety and differences in growth conditions might explain these different observations. Additionally, isoforms of enzymes may play different roles at a particular developmental stage (Chaturvedi et al, 2013; Ischebeck et al, 2014; Wang et al, 2016a,b), thus displaying varying dynamics during development. For instance, Fraige et al reported three isoforms of UDPase, of which two candidates decreased in abundance after veraison whereas one increased (Fraige et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variety and differences in growth conditions might explain these different observations. Additionally, isoforms of enzymes may play different roles at a particular developmental stage (Chaturvedi et al, 2013; Ischebeck et al, 2014; Wang et al, 2016a,b), thus displaying varying dynamics during development. For instance, Fraige et al reported three isoforms of UDPase, of which two candidates decreased in abundance after veraison whereas one increased (Fraige et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Significant different metabolites in flavonoid biosynthetic pathway were reported in purple fig mutation compared to the green control [23]. The interaction of the primary and secondary metabolites profiles combined with proteomics elucidated the accumulation of phenolic substances and other major compounds related to flavonoids accumulation during seed development in cacao [25].Over the past decade, studies related to red-fleshed apple were mainly focused on the structural and regulatory genes which play important roles in anthocyanins biosynthesis [26][27][28][29]. Little attention was paid to the identification and classification of metabolites of red-fleshed apple.…”
mentioning
confidence: 99%
“…Significant different metabolites in flavonoid biosynthetic pathway were reported in purple fig mutation compared to the green control [23]. The interaction of the primary and secondary metabolites profiles combined with proteomics elucidated the accumulation of phenolic substances and other major compounds related to flavonoids accumulation during seed development in cacao [25].…”
mentioning
confidence: 99%
“…Untargeted metabolic fingerprinting of gas chromatography-mass spectrometry (GC-MS) or liquid chromatography-mass spectrometry (LC-MS) data coupled with chemometrics has proven to be a robust tool for multiplex metabolomic profiling from a global perspective [13,14]. In a typical analysis, tens of thousands of metabolites can be measured by LC-MS in the anaerobic digestate of manure [15].…”
Section: Introductionmentioning
confidence: 99%